2016
DOI: 10.1080/02673843.2016.1267021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of life satisfaction on substance abuse: delinquency as a mediator

Abstract: The objectives of the study were two-folds: firstly, to ascertain the effect of life satisfaction on substance abuse among Malay youth. Secondly, to identify the role of delinquency on the relationship between life satisfaction and substance abuse. Self-administered questionnaires were distributed among youths at the youth programmes using a two-step sampling technique: area sampling and systematic sampling. The research hypotheses were tested using Structural Equation Modelling. The findings of the study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 44 publications
3
52
0
1
Order By: Relevance
“…Confirmatory Factor Analysis (CFA) was used to validate the measurement model. There are three types of validity tests; construct validity, convergent validity and discriminant validity (Mohamad et al, 2018). Construct validity was assessed by using goodness-of-fit indices.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmatory Factor Analysis (CFA) was used to validate the measurement model. There are three types of validity tests; construct validity, convergent validity and discriminant validity (Mohamad et al, 2018). Construct validity was assessed by using goodness-of-fit indices.…”
Section: Discussionmentioning
confidence: 99%
“…It was stated by Doherty, Green & Ensminger (2008) that delinquent behavior was highest in late adolescence (age 17-18) and it declined in adulthood. It was also observed that delinquent youths tend to be more drug involved than non-delinquent youths (Brunelle et al, 2014); Mohamad et al, 2018). Delinquency, behaving in a way that was illegal or not acceptable by the general society, was an anti-social behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During this stage, individuals were deemed to be dependent on family for emotional and economic support (Furlong, 2013). In Malaysia, youth was categorized as individuals aged between 15 and 40 years old (Mohamad, Mohammad, Ali & Awang, 2018). For some youth, this phase of life was the most challenging and stressful period, dealing with the pressure arising from their desire to be independent whereas, at the same time, they were still depending on families for support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convergent Validity, which is evaluated through Average Variance Extracted. The construct reliability (CR) is evaluated through computing CR value for every construct(Awang et al, 2018;Afthanorhan et al, 2018;Mohamad et al, 2017Mohamad et al, , 2018Mohamad et al, , 2019. The Confirmatory Factor Analysis outputs are presented inFigure 2.…”
mentioning
confidence: 99%